HAND HYGIENE KNOWLEDGE AMONG HOSPITAL HEALTH WORKERS IN PALEMBANG DURING COVID-19 ERA - Haerawati Idris; Rizma Adlia Syakurah; Dian Safriantini (Indonesian Journal of Health Administration, 2021)
Background: Hand hygiene is the simplest practical method of preventing cross-infection. Knowledge of hand hygiene plays a vital role in determining adherence to hand hygiene. Nosocomial infection is an infection that occurs in patients in hospital.Aims: This study aims to analyze the knowledge of health workers regarding hand hygiene in Palembang hospitals during Covid-19 era.Methods: This study used a cross-sectional design with 300 health workers who worked in hospitals in Palembang. They are selected by simple random sampling. Data were collected using online questionnaire during October 2020.Results: The majority of respondents were female (88.67%), with the majority age group 30-39 years (43.67%), the majority of respondent came from nurses (63%), work in inpatient rooms (27.33%). A total of 80.67% of respondents have received formal training related to hand hygiene. 96% used alcohol-based hand rub. About 15.33% of respondents indicated good knowledge, moderate knowledge (80.33%), and less knowledge (4.3%) regarding hand hygiene. The difference in health workers' profession was significantly related to the level of knowledge about hand hygiene (p <0.05).Conclusion: There are differences in the level of knowledge about hand hygiene in each type of health worker professionKeywords: Hand Hygiene; Knowledge; Health Workers; Online